Republic of Belarus : Technical Assistance Report-Enhancing Monetary Policy Modeling Capacity, Monetary Policy Implementation, and the Forecasting and Policy Analysis System. (IMF Staff Country Reports; Country Report ;, 2020)
The NBRB has made substantial progress in improving its forecasting and policy analysis system (FPAS) and integrating it into monetary policy decision-making. The FPAS, and the model-based forecasts and policy analysis, is now well integrated into the policy-making process. Staff are well trained and have become experienced in using the tools developed for policy analysis and forecasting. The forecasting and decision-making process is well structured and has helped increase the two-way interaction between staff and the NBRB board-additional and less formal interaction between staff and board members in between the formal meetings may help enhance the process further.